Phenomenology of Personal Financial Balance and Fandom Expenditure Through Merchandise Jasa Titip Among Generation Z - Bella Sripuspita; Alisya Putri Salsabil; Cindi Apriany; Nabila Khaerunnisa (The Future of Education Journal, 2026)
This study aims to explore in depth how Generation Z in Indonesia balances personal finances amid fandom-related spending facilitated by personal shopper (jastip) services for merchandise purchases. Employing a phenomenological approach, the study conducted in-depth interviews with eight informants aged 18 to 26 years who were active members of K-Pop fan communities and regular users of personal shopper services. The findings reveal three major themes: (1) the rationalization of fandom expenditures as an investment in personal identity, (2) adaptive financial management strategies developed independently by fans, and (3) the influence of community-driven social pressure on impulsive purchasing decisions through personal shopper services. The results indicate that participants developed informal mental accounting systems to separate fandom-related expenses from primary living needs. However, these self-imposed financial boundaries were frequently challenged when exclusive merchandise pre-orders became available. The study highlights the complex interaction between personal identity, consumer behavior, and financial decision-making among Generation Z fans. Furthermore, it demonstrates how fandom participation shapes financial priorities while simultaneously encouraging the development of adaptive budgeting strategies. This research contributes to the growing literature on Generation Z financial behavior and opens further discussion regarding the need for financial literacy programs that are contextualized to contemporary fandom lifestyles and digital consumer culture.